The SAGE handbook of research on teacher education - Clandinin, D. Jean; Husu, Jukku (London : SAGE Publications Ltd, 2017)
The SAGE handbook of research on teacher education offers an ambitious and international overview of the current landscape of teacher education research, as well as the imagined futures. The two volumes are divided into sub-sections: Section one: Mapping the landscape of teacher education, Section two: Learning teacher identity in teacher education, Section three: Learning teacher agency in teacher education, Section four: Learning moral & ethical responsibilities of teaching in teacher education, Section five: Learning to negotiate social, political, and cultural responsibilities of teaching in teacher education, Section six: Learning through pedagogies in teacher education, Section seven: Learning the contents of teaching in teacher education, Section eight: Learning professional competencies in teacher education and throughout the career, Section nine: Learning with and from assessments in teacher ...
Description based on MARC record for print version.
Includes index.
Keywords: Teachers -- Training of -- United States; Teaching -- Handbooks, manuals, etc